THE CAUSE-AND-EFFECT PRINCIPLE: OPACITY OF SLAVERY IN TONI MORRISON’S BELOVED - SANTHOSH, S. LAKSHMAN; MAHALAKSHMI, S. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
When Toni Morrison embarked on her exploration of slavery, she grappled with two crucial inquiries. The first question delved into the resilience of her nation in enduring the unimaginable cruelties inflicted upon them. The second question probed the conspicuous absence of any mention in European historical records regarding the origins of the slave trade and the subsequent forced migration. The novel is a fearful picture of how bestiality and cruelty could come together to question the crude practices of sexual exploitation, emotional breakdown and physical torture in the name of developing the Western economy. The paper is an attempt to look at the circumstances that gave way to the genesis of one of the most important forerunners of slavery and its repercussions.